Design And Development Of Automatic Fiber Optic Cable Roller Using Nodemcu Esp 8266 Module - Widodo .; Nur Hidayat (BEST, 2022)
ABSTRACT The process of winding fiber optic cable rolls takes a long time because it is done manually or conventionally. One of the tools in winding is a FO cable roller. This tool is designed to be able to roll fiber optic cables, but the limitations of this tool are still done manually, FO cables are rolled by hand like pedaling a bicycle on the pedals, the speed is set based on the speed of the rotation of the hand and it all depends on the human factor. Therefore, there is a need for an Automatic Fiber Optic Cable Winder Using NodeMCU ESP8266 and using Iot (Web of Things) to be more efficient and better in cable winding expositions.